Current trends in large‐scale viral surveillance methods in mosquitoes. Issue 6 (29th June 2020) - Park, Ki Beom; Patnaik, Hongray Howrelia; Kim, Tae‐Yun; Jo, Yong Hun; Kim, Nam‐Yeon; Yang, Sung‐Chan; Lee, Wook‐Gyo; Lee, Hee‐Il; Cho, Shin‐Hyeong; Han, Yeon Soo
Abstract: Vector‐borne and zoonotic infectious diseases are serious public health concerns that affect approximately half of the world's population. In particular, arthropod‐borne viruses (arboviruses) have contributed to more mortality and morbidity worldwide with the emergence of dengue, chikungunya, yellow fever, and Zika virus diseases. The infections have scaled up due to urbanization, globalization, and international mobility. Traditionally, the spread of mosquito‐borne viral diseases to humans was considered a low health priority concern. However, their categorization as emerging infectious diseases and public health emergencies of international concern has heightened the attention given by the government, academia, research, and industry for the development of timely, cost‐efficient, and sustainable solutions. The urgency has increased in the wake of global climate change. The focus on effective interventions includes epidemiological monitoring, vector control measures, molecular diagnostics, vaccines, and environmental determinants. In this review, we discuss the etiology and predisposition of mosquito‐borne viruses that are detrimental to public health and economically damaging when disseminated as epidemics. We focus on the large‐scale virus surveillance methods with special reference to innovations and interventions in molecular detection science and technologies that include viral nucleic acid isolation, polymerase chain reaction (PCR)‐based diagnostics, and high‐throughput sequencing technologies. In addition, we discuss the development of a viral RNA extraction and PCR‐based diagnostic kit (Invirustech) that can extract viral RNA from mosquitoes with verified applications in PCR‐based molecular diagnostics of Pan‐flavivirus.